Comparative Study & Efficacy of Commonly Used Disinfectant against Human Pathogens - Deolekar, Minal A.; Khapekar, Shraddha (International Journal of Scientific Research in Biological Sciences, 2021)
Disinfection is the process of elimination of virtually all pathogenic organism on inanimate objects & surfaces thereby reducing the level of microbial contamination to safe level.The study aimed to evaluate sensitivity of some clinical organisms used for the tests are S. aureus, Klebshiella , Pseudomonas, E. coli, Bacillus with the activity of some selected commercial disinfectants used are Dettol, Lysol, Ultraclean, Phenyl & Phenol. All the disinfectants used in this study have bactericidal effect against the test organisms whereas Phenol Coefficient test was carried out to compare sensitivity of disinfectants to that of phenol under experimental method so as to determine the disinfectant efficacy. Phenol & Dettol showed highest antimicrobial activity against all test organisms. Ultraclean also showed high antimicrobial activity except Pseudomonas aeuroginosa. Phenol coefficient test was used for Staphylococcus appear as Lysol is the most potent disinfectant than all other disinfectant and for Bacillus appear as Dettol is more effective than other disinfectant used in this study.